Can the salivary urea and stimulated saliva concentration be a marker of periodontal diseases in opioid users? A case-control study - Parvin parvaei; Marzie eydzadeh; Freshteh Osmani (Heliyon, 2023)
Introduction: & Aim: Microbial plaque is the primary cause of periodontal diseases, and smoking and opioid addiction can accelerate microbial plaque formation and disease progression. Adequate saliva flow and salivary urea concentration are important parameters for a healthy periodontium. In this study, the relationship between Periodontal Diseases and the History of opioid addiction was investigated by measuring the Salivary Urea and Stimulated Saliva Concentration. Materials & methods: This case-control study was conducted on 240 patients (120 cases and 120 controls) in 2021 referred to addiction treatment centers and the dental clinic in Iran, Birjand. The control and case groups were matched in terms of age. Demographic, base data, and clinical examination results were collected by a checklist. Data were analyzed using SPSS 19 and one-way ANOVA and chi-square tests. P-value <0.05 was considered as the significance level. Results: Periodontitis severity was significantly higher in the case group than in the control group (P-value = 0/000). Salivary urea concentration significantly increased in both case and control groups with an increase in periodontitis severity (P-value = 0/003 in the case group and P-value = 0/000 in the control group), but there was no significant relationship between the stimulated saliva flow rate and the severity of periodontitis in these two groups (P-value>0.05). Conclusion: Following the use of opioids, the flow of saliva decreases, and with the exacerbation of the periodontal disease, the concentration of urea in saliva increases. Therefore, it seems that the analysis of saliva parameters, including urea concentration, can be useful for the diagnosis of periodontal disease, and saliva urea concentration is not directly related to opioid use.